(untitled) (Communications in Mathematical Research, 2021)
In this work we discuss the existence of Ψ-bounded solutions for linear difference equations. We present a necessary and sufficient condition for the existence of Ψ-bounded solutions for the linear nonhomogeneous difference equation x(n+1) = A(n) x(n) + f(n) for every Ψ-bounded sequence f(n).